2001
DOI: 10.1063/1.1350661
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity of the liquid–liquid mixture perfluoroheptane and 2,2,4-trimethylpentane near the critical point

Abstract: The heat capacity of the liquid–liquid mixture perfluoroheptane and 2,2,4-trimethylpentane (also known as iso-octane) has been measured for the first time near its upper critical consolute point using an adiabatic calorimeter. The theoretical expression for the heat capacity near the critical point was applied to our combined data runs. The critical exponent α was determined to be 0.106±0.026, which agreed with theoretical predictions. When α was fixed at its theoretical value of 0.11, our value for the amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It was found that the variation of 0.01 in a caused the changes of about 16%, 11%, 5%, and 1.6% in A + , A À , A + /A À , and C p0 , respectively, while the contribution of the variations of T c and E within their uncertainties to the changes of the adjusting parameters were negligible. It was reported that the theoretical predictions gave the values of A + /A À being (0.537 ± 0.019) for d = 3 expansion [1], (0.530 ± 0.003) for high-temperature series [2], (0.527 ± 0.037) for e expansion [1], and (0.55 ± 0.01) for Monte Carlo simulation [33], while the experimental values were ranged between 0.52 and 0.59 [26,28,30,32,[34][35][36][37][38][39]. The value of A + /A À determined in this study in the temperature range of ±2.8 K from the critical point is 0.533, which is in excellent agreement with the theoretical prediction of 0.530 for hightemperature series.…”
Section: Isobaric Heat Capacity Per Unit Volumementioning
confidence: 97%
“…It was found that the variation of 0.01 in a caused the changes of about 16%, 11%, 5%, and 1.6% in A + , A À , A + /A À , and C p0 , respectively, while the contribution of the variations of T c and E within their uncertainties to the changes of the adjusting parameters were negligible. It was reported that the theoretical predictions gave the values of A + /A À being (0.537 ± 0.019) for d = 3 expansion [1], (0.530 ± 0.003) for high-temperature series [2], (0.527 ± 0.037) for e expansion [1], and (0.55 ± 0.01) for Monte Carlo simulation [33], while the experimental values were ranged between 0.52 and 0.59 [26,28,30,32,[34][35][36][37][38][39]. The value of A + /A À determined in this study in the temperature range of ±2.8 K from the critical point is 0.533, which is in excellent agreement with the theoretical prediction of 0.530 for hightemperature series.…”
Section: Isobaric Heat Capacity Per Unit Volumementioning
confidence: 97%
“…The experimental values of this ratio reported in literatures varied from 0.009 to 0.033 [37,[44][45][46][47]. Substitution of the values of A + determined from heat capacity measurements (0.01385 ± 0.00002) J Á K À1 Á cm À3 and n 0 (0.275 ± 0.006) nm determined from the turbidity measurements into equation (29) yielded a value of the two-scale-factor universality ratio being 0.021 ± 0.002.…”
Section: Tablementioning
confidence: 98%
“…A later measurement by Pittois et al 17 confirmed the heat capacity data and results for that system. Oby et al 11 measured the heat capacity of perfluoroheptane and 2,2,4-trimethylpentane and found X = 0.009± 0.002 when using the literature value for the correlation length amplitude. More recently, Souto-Caride et al 20 measured the heat capacity and viscosity for the alkanes hexane, heptane, and octane when mixed with nitrobenzene.…”
Section: Introductionmentioning
confidence: 99%